Impact of wait times for treatment on clinical outcomes in patients with obstructive sleep apnoea: protocol for a randomised controlled trial. Issue 2 (20th June 2022) - Thornton, Christina S.; Povitz, Marcus; Tsai, Willis H.; Loewen, Andrea H.; Ip-Buting, Ada; Kendzerska, Tetyana; Flemons, W. Ward; Fraser, Kristin L.; Hanly, Patrick J.; Pendharkar, Sachin R.
Background: Obstructive sleep apnoea (OSA) is a common chronic condition that is associated with significant morbidity and economic cost. Prolonged wait times are increasingly being recognised as a barrier to diagnosis and treatment of many chronic diseases; however, no study to date has prospectively evaluated the impact of wait times on health outcomes in OSA. Objective: The purpose of this study is to determine whether treatment outcomes for individuals with OSA differ between patients managed using an expedited versus standard pathway. Methods: A pragmatic randomised controlled trial design will be used with a target sample size of 200 adults. Participants with clinically significant uncomplicated OSA will be recruited through referrals to a large tertiary care sleep centre (Calgary, AB, Canada) and randomised to either early management (within 1 month) or usual care (∼6 months) with a 1:1 allocation using a concealed computer-generated randomisation sequence. The primary outcome will be adherence to positive airway pressure (PAP) therapy at 3 months after treatment initiation. Secondary outcomes will include change in sleepiness, quality of life, patient satisfaction, and patient engagement with therapy from baseline to 3 months after PAP initiation, measured using validated questionnaires and qualitative methods. Anticipated results: This study will determine whether expedited care for OSA leads to differences in PAP adherence and/or patient-reported outcomes. More broadly, the findings of this study may improve the understanding of how wait time reductions impact health outcomes for other chronic diseases. This study will determine whether expedited care for OSA leads to differences in PAP adherence and/or patient-reported outcomes https://bit.ly/38TrkwS